How Does Taxation Affect Hours Worked in EU New Member States? - Velasquez, Agustin (IMF Working Papers; Working Paper ;, 2019)
Hours worked vary widely across countries and over time. In this paper, we investigate the role played by taxation in explaining these differences for EU New Member States. By extending a standard growth model with novel data on consumption and labor taxes, we assess the evolution of trends in hours worked over the 1995-2017 period. We find that the inclusion of tax rates in the model significantly improves the tracking of hours. We also estimate the elasticity of hours (and its different margins) to quantify the deadweight loss introduced by consumption and labor taxes. We find that these taxes explain a large share of labor supply differences across EU New Member States and that the potential gains from policy actions are noteworthy.